The relationship of biochemical parameters and radiological parameters in the evaluation of the clinical severity of acute pancreatitis in the emergency department – a retrospective analysis - Tortum, Fatma; Tekin, Erdal; Aydın, Fahri; Özdal, Emine; Tatlısu, Kübra (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Computed tomography severity index (CTSI) and Balthazar score are among the most frequently used scorings in the determination of severe acute pancreatitis. The primary purpose of this study is evaluation of the effects of biochemical parameters, Balthazar score and CTSI on mortality in acute pancreatitis. At the same time, correlations with biochemical parameters, CTSI and Balthazar score were evaluated in patients with AP. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. In this study, the amylase, lipase, CRP, and procalcitonin values of patients diagnosed with acute pancreatitis were retrospectively recorded. Contrast-enhanced computed tomography (CECT) images obtained at the time of presentation to the emergency department or within seven days of admission were re-evaluated by two radiologists. The CTSI scores and Balthazar scores of the patients were calculated. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The study included 240 patients. The amylase level of the patients was positively correlated with the Balthazar score at a statistically significant level (R=0.189, p=0.003). In addition,, the relationship between pancreatic scoring systems and mortality, the AUC value for CTSI was 0.9 (95% CI: 0.826-0.973) and was higher than other scoring systems. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. CTSI had better performance in the prediction of mortality in patients with acute pancreatitis.